2017
DOI: 10.1016/j.scitotenv.2016.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cu stabilization and biomass yields of Giant reed and poplar after adding a biochar, alone or with iron grit, into a contaminated soil from a wood preservation site

Abstract: A 2-year pot experiment was carried out to examine the aging effect of biochar (B), alone or combined with iron grit (Z), on Cu stabilization and plant growth in a contaminated soil (964mg Cu kg) from a wood preservation site. The experiment consisted in 3 soil treatments, either planted with Arundo donax L. (Ad) or Populus nigra L. (Pn): (1) untreated Cu-contaminated soil (Ad, Pn); (2) Unt+1% (w/w) B (AdB, PnB), and (3) Unt+1% B+1% Z (AdBZ, PnBZ). After 22months, the soil pore water (SPW) was sampled and root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…This raises the question of whether or not the observed biochar effect would diminish over time. Also, organic acids released from plants grown at a site could potentially lead to a release of Cu from biochar (Oustriere et al, 2017), which would be problematic, since long-term stability of the amendments is crucial for remediation. Furthermore, flooding, which was frequently observed at this study site, could be problematic; under anaerobic conditions biochar has been shown to enhance As mobilization, possibly by acting as an electron shuttle (Kappler et al, 2014;Wang et al, 2017).…”
Section: Effects Of Soil Amendments On Soil Qualitymentioning
confidence: 99%
“…This raises the question of whether or not the observed biochar effect would diminish over time. Also, organic acids released from plants grown at a site could potentially lead to a release of Cu from biochar (Oustriere et al, 2017), which would be problematic, since long-term stability of the amendments is crucial for remediation. Furthermore, flooding, which was frequently observed at this study site, could be problematic; under anaerobic conditions biochar has been shown to enhance As mobilization, possibly by acting as an electron shuttle (Kappler et al, 2014;Wang et al, 2017).…”
Section: Effects Of Soil Amendments On Soil Qualitymentioning
confidence: 99%
“…The giant reed (Arundo donax L.) has been proposed as a promising candidate for phytoremediation due to its favorable characteristics as a biomass crop [15][16][17][18][19]: rapid growth and high production of biomass; simple agronomic management and easy harvesting of biomass; good tolerance and ability to assimilate the metals, preferably in the aboveground biomass [20,21]. The present work aimed to evaluate the physiological response of Arundo in a semi-hydroponic growing system in on-field environmental conditions (mesocosm) contaminated with different concentrations of Cu (0, 150, and 300 ppm).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to A. donax, Miscanthus was also reported to be suitable for phytoremediation of heavy metals, such as Cd, Co, Cu, Fe, Ni, Pb, Zn [21,102,104,[125][126][127][128][143][144][145]. Miscanthus was planted on soils contaminated by the Chernobyl nuclear accident [146] and used for revitalisation of mining brownfields in Slovakia [147].…”
Section: Resultsmentioning
confidence: 99%